Transcriptomic profiling in Musa: a look into processes affected by mild osmotic stress in the root tip - Zorrilla-Fontanesi, Yasmín; Rouard, M.; Cenci, A.; Kissel, E.; Do, H.; Dubois, E.; Nidelet, S.; Roux, N.; Swennen, Rony L.; Carpentier, Sebastien C. (2016)
Drought stress is one of the major abiotic factors limiting banana (Musa) production. Even mild-drought conditions are responsible for considerable yield losses. We performed large-scale transcriptome sequencing using Illumina technology on root tissue of three triploid genotypes representing well known cultivars and focused on the identification of genes with an altered expression pattern under mild osmotic stress (3 days after 5% PEG treatment). In total, 18 cDNA libraries were sequenced producing around 568 million high quality reads, of which 70-84% were mapped to the diploid reference genome (D’Hont et al., 2012). Through uni-/multivariate statistics, 92 genes were commonly identified as differentially expressed in the three genotypes. Using our in house workflow to analyze GO enriched and underlying biochemical pathways, we present a panorama of the general processes affected by mild osmotic stress in the root tip, although we observe a bias towards glycolysis and fermentation. We hypothesize that in this fast growing and oxygen demanding tissue, mild osmotic stress leads to a lower energy level, which induces a metabolic shift towards (i) a higher oxidative respiration, (ii) alternative respiration and (iii) fermentation. To validate the mRNA-seq results, a subset of twenty up-regulated genes were further analyzed at three different time points (6 hours, 3 days and 7 days) in an independent PEG experiment. Overall, the identification and annotation of this set of genes constitutes a step ahead to understand the complex network of root responses to osmotic (drought) stress.